2014
DOI: 10.3389/fendo.2014.00210
|View full text |Cite
|
Sign up to set email alerts
|

Humanin and Age-Related Diseases: A New Link?

Abstract: Humanin (HN) is 24-amino acid mitochondria-associated peptide. Since its initial discovery over a decade ago, a role for HN has been reported in many biological processes such as apoptosis, cell survival, substrate metabolism, inflammatory response, and response to stressors such as oxidative stress, ischemia, and starvation. HN and its potent analogs have been shown to have beneficial effects in many age-related diseases including Alzheimer’s disease, stroke, diabetes, myocardial ischemia and reperfusion, ath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(100 citation statements)
references
References 106 publications
3
96
0
1
Order By: Relevance
“…We found significant upregulation of genes involved in glycolytic pathways in cardiomyocytes subjected to hypoxia demonstrating a shift in energy production from mitochondria to glycolysis (Jian et al , 2011b). Recently it has been found that humanin, a mitochondria derived peptide, exhibits strong cytoprotective actions against various stress and disease models and suggested to be part of a retrograde signaling that involves nuclear-mitochondria crosstalk (Gong et al , 2014). This inter-organelle communication is important in the mitochondrial response to hypoxic-ischemic conditions, whether induced by stroke, myocardial-infarction or sepsis.…”
Section: Hypoxic-ischemic Injurymentioning
confidence: 99%
“…We found significant upregulation of genes involved in glycolytic pathways in cardiomyocytes subjected to hypoxia demonstrating a shift in energy production from mitochondria to glycolysis (Jian et al , 2011b). Recently it has been found that humanin, a mitochondria derived peptide, exhibits strong cytoprotective actions against various stress and disease models and suggested to be part of a retrograde signaling that involves nuclear-mitochondria crosstalk (Gong et al , 2014). This inter-organelle communication is important in the mitochondrial response to hypoxic-ischemic conditions, whether induced by stroke, myocardial-infarction or sepsis.…”
Section: Hypoxic-ischemic Injurymentioning
confidence: 99%
“…The extracellular actions of humanin are largely mediated through its cell membrane receptors (16 -17). Humanin has potent neuroprotective (18), antiapoptotic (19), and IGFBP3-binding (20) cytoprotective effects with broad-spectrum actions on the brain, pancreas, heart, and testis (21)(22). Eriksson and colleagues (23) recently showed that cotreatment of a potent humanin analog HNG with a proteasome inhibitor bortezomib was effective in preventing bortezomib-induced bone growth impairment without interfering with bortezomib's anticancer effects in immune deficient nude mice.…”
mentioning
confidence: 99%
“…Mitochondrially translated humanin has 21 amino acids; the one translated in the cytosol is has 24 amino acids [108]. A recent review by Gong et al has described the neuro- and cytoprotective roles of humanin in human conditions such as Alzheimer’s disease, Huntington’s disease, prion disease, atherosclerosis, diabetes, and aging [31]. …”
Section: Historical Aspects Of Numtogenesismentioning
confidence: 99%